Self-Esteem, Hope, and Suicidal Ideation Among University Students - Sofia Tri Putri; Dinar Saputra; Destria Maharani (Greenation Publisher & Yayasan Global Research National, 2026)
Suicidal ideation among university students has become an increasing mental health concern, highlighting the need to identify psychological factors that may protect against its development. This study investigated the associations of self-esteem and hope with suicidal ideation among university students using a quantitative correlational design. Data were analyzed using Spearman's rank-order correlation. The findings revealed significant negative relationships between both psychological variables and suicidal ideation. Self-esteem was negatively associated with suicidal ideation (rs = −0.399, p < 0.001), indicating that students with higher self-esteem reported lower levels of suicidal ideation. Similarly, hope showed a significant negative correlation with suicidal ideation (rs = −0.322, p < 0.001). Overall, the findings suggest that self-esteem and hope function as protective psychological resources that may reduce the likelihood of suicidal ideation among university students. These results highlight the importance of strengthening positive psychological resources as part of mental health promotion and suicide prevention efforts in higher education.